Leaders in Communicating and Maintaining Sustainable Academic Culture Toward the Top Ten Universities in Indonesia - TRENGGONO, NANANG; SULISTYARINI, DHANIK; WARDHANI, ANDY CORRY; ZAINAL, ANNA GUSTINA; ., SURIPTO (Journal of Ecohumanism, 2024)
For universities, leader performance is a determining factor for success. Organizational culture grows with the organization's leaders. In addition, there is a tendency to change the organizational culture perspective towards subjectivism (Clark, Geertz, Schwartz & Ogilvy, Weick). For the University of Lampung (Unila), which was founded in 1965, it turns out that leaders' communication performance under pressure of problems can maintain its academic culture. Initially, this research began with a decrease in Unila's ranking among Indonesian universities in 2019. After conducting the study, two cultural orientations were found, which are being a research university and an educational university. These two value orientations have the power to increase Unila's ranking among universities, as well as becoming a legacy. In 2022 there was a corruption case by university leaders, accepting bribes in admitting new students. The research continues with a focus on how a guided communication culture can maintain Unila's ranking. Data collection was carried out through intensive interviews with the new rector, vice rectors and faculty deans. The results show a picture of typical leader communication patterns, to maintain a sustainable academic culture. First, in the context of recovery, prioritizing internal communication patterns through ritual activities. Second, the slogan “Be Strong” was symbolically proclaimed within the academic community. Third, the communication pattern that is practiced both in the leadership ranks through the division of roles and among all members is to create togetherness, support each other, and reduce structural barriers.